Increasingly Equalized? A Study of Part-Time Work in ‘Old’ and ‘New’ Part-Time Work Regimes - Nicolaisen, Heidi (Nordic Journal of Working Life Studies, 2011)
Recent debates on equalization of part-time work alongside full-time work stress the importance of high quality part-time jobs. This paper compares equalization in banking in three countries: two `old´ part-time work regimes, Norway and Sweden, and Ireland, where part-time work started to increase more recently. Banking is particularly interesting as a sector with a high proportion of female employment and good working conditions. One main interest is the role of regulations and how they are enforced at company level. The analysis shows that part-time work in the Nordic countries is normalized in terms of access and general work conditions, while in Ireland access is more restricted. Career opportunities are, however, restricted in all three countries. This paper argues that further equalization may be hindered by `soft´ regulations and a gradual normalization process that also normalizes disadvantages associated with part-time work and the category of the `working mother´.